Seasonal variation in fresh fruit bunch production in dura oil palm - PRATHAPANI, NAVEEN KUMAR; MATHUR, RAVI KUMAR; MURUGESAN, PITCHAI; A, GOPAL KRISHNA REDDY; K, SUNILKUMAR; D, RAMAJAYAM; G, RAVICHANDRAN (The Indian Journal of Agricultural Sciences, 2017)
An attempt was made to study the temporal variation in the Fresh Fruit Bunche’s (FFB) production in dura palms at Indian Institute of Oil Palm Research, Pedavegi, Andhra Pradesh. The performance of the two D × D cross combinations, viz. 240D × 281D (CC1 palms) and 80D × 281D (CC2 palms) planted in the year 2000 in terms of number and weight of fresh bunch produced during different months during 2005 – 2012 was analysed. The FFB production (in terms of number and weight) was maximum (seasonal maxima) during the four months from May to August in an year which accounted for almost 2/3rd of FFB production of the year. Seasonal minima in the FFB production was observed during the winter starting from October to March. FFB production exhibited a trend of alternate bearing that is good yield in one year (on year) and reduced or poor yield in the subsequent year (off year), the trend being consistent in respect of bunch weight. The average bunch weight continuously increased from the 6th to 13th year of the plantation. The difference in FFB production not significantly different whereas the duration of FFB production (seasonal maxima) was significantly different among crosses. In Andhra Pradesh, it could be the non-availability of short days or non-availability of pollen and or pollinating weevil during rainy season (June to October in Andhra Pradesh) resulting in reduced flowering and subsequently low harvest of FFB (after 5-6 months of flowering) during November to March (Seasonal minima).